2020
DOI: 10.3390/s20143924
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides as the Sensing Material for Metal Ion Detection-Based Optical Sensor Applications

Abstract: The incorporation of a proper sensing material towards the construction of high selectivity optical sensing devices is vital. Polysaccharides, such as chitosan and carrageenan, are among the bio-based sensing materials that are extensively employed due to their remarkable physicochemical attributes. This paper highlights the critical aspects of the design of suitable polysaccharides for the recognition of specific analytes through physical and chemical modifications of polysaccharide structure. Such modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 82 publications
1
31
0
1
Order By: Relevance
“…The pattern of current research focuses on biopolymer polysaccharides as sensors, polymer electrolytes, and biological applications through the enhancement of active sites such as cellulose, chitosan, and carrageenan [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Modification of active sites in a biopolymer polysaccharide structure is vital for the enhancement of the polysaccharide’s performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pattern of current research focuses on biopolymer polysaccharides as sensors, polymer electrolytes, and biological applications through the enhancement of active sites such as cellulose, chitosan, and carrageenan [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Modification of active sites in a biopolymer polysaccharide structure is vital for the enhancement of the polysaccharide’s performance.…”
Section: Introductionmentioning
confidence: 99%
“…Mobarak et al [ 6 ] synthesized carboxymethyl carrageenan and claimed substitution of the carboxymethyl group enhanced its physiochemical properties. They reported that the ionic conductivity of modified carrageenan increased by three orders of magnitude as compared to pristine carrageenan [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, photonics integration, microfluidics, and microelectronics on a single chip provide an attractive technical foundation for implementing lab-on-a-chip systems, which are critical for performing quick, multiplexed, and real-time experiments and a variety of application sectors [ 22 ]. Recent studies have explored developing sensors based on photonics such as visible-light laser diodes, infrared analytics arrays, narrowband optical filters, surface plasmonic resonance (SPR), surface-enhanced Raman scattering (SERS), fluorescence, and other laser techniques, in order to solve many of the challenges of biological detection [ 23 , 24 , 25 , 26 ]. A study showed optical biosensors based on a combined Mach–Zehnder interferometer.…”
Section: Introductionmentioning
confidence: 99%
“…They have advantages such as reducing waste, low cost preparation, ease of use and in situ analysis. Some materials have been used for the optical sensor's matrix such as polyvinyl chloride (PVC) [3], agarose [4], polyvinyl acetate (PVA) [5,6], chitosan, ethyl cellulose [7], and polysaccharide [8]. In addition, sol-gel matrix was used as polymer the matrix to immobilize the reagent for metal ion determination [9].…”
Section: Introductionmentioning
confidence: 99%